The effects of categorical similarity and feature-space proximity on visual working memory processing. Issue 2 (7th February 2018) - Yang, Li; Mo, Lei; Wang, Xingchao; Yu, Mengxia
ABSTRACT: Two patterns of data predict that similarity has a positive effect and a negative effect on visual working memory (VWM) processing. We assume that these two empirical outcomes do not distinguish categorical similarity from feature-space proximity, resulting in this divergence. To investigate how categorical similarity and feature-space proximity modulate VWM, we tested memory for an array of pictures drawn from either mixed categories or a single category in which feature-space proximity varied along a morph continuum in a change-detection task. We found that memory under the mixed-category condition was better than that under the single-category condition, whereas memory under high feature-space proximity was superior to that under low feature-space proximity. These patterns were unaffected by manipulations of stimulus type (faces or scenes), encoding duration (limited or self-paced), and presentation format (simultaneous or sequential). These results are consistent with our hypotheses that categorical similarity inhibits VWM, whereas feature-space proximity facilitates VWM. We also found that memory for items with low feature-space proximity benefited more from mixed-category encoding than that for items with high feature-space proximity. Memory for faces benefited more from mixed-category encoding than scenes, whereas memory for scenes benefited more from feature-space proximity than faces. These results suggest that centre-surround inhibition organization might underlie similarity effects in VWM. Centre-surround inhibition organization for complex real-world objects could have both categorical level and feature-space level. The feature-space level might differ by category.